2014
DOI: 10.1111/1750-3841.12505
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Fresh and Dried Figs from Cilento (Italy), by Considering Breba Crop and Full Crop, in Comparison to Turkish and Greek Dried Figs

Abstract: The results of this research could be useful to deepen the knowledge about the phenolic composition of a fruit that is particularly appreciated in Mediterranean area and presents an increasing interest worldwide. We also characterized a typical Italian fig (Cilento Dottato) that has relevant economical importance in Southern Italy; thus, our work could be applied by producers and industries for the valorization of dried figs as high-quality products. From the consumer viewpoint, a comparison among dried figs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
6
28
1
2
Order By: Relevance
“…cuello de dama. The results obtained in this work are in agreement with several studies which reported that the main flavonoid present in fig fruits is rutin (Veberic et al, 2008a;Russo et al, 2014). However, in these studies the values obtained for rutin were higher than obtained in this work.…”
Section: Polyphenolic Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…cuello de dama. The results obtained in this work are in agreement with several studies which reported that the main flavonoid present in fig fruits is rutin (Veberic et al, 2008a;Russo et al, 2014). However, in these studies the values obtained for rutin were higher than obtained in this work.…”
Section: Polyphenolic Profilesupporting
confidence: 92%
“…cuello de dama. The values obtained for this compound were higher than reported by Russo et al (2014) in figs cv. dottato cultivated in Italy.…”
Section: Polyphenolic Profilecontrasting
confidence: 72%
“…contains polyphenols, organic acids, and free amino acids [35][36][37]. Fig (Ficus carica L.) possesses antioxidant activity and is a source of phenolic and flavonoid compounds, alkaloids, terpenoids, and saponins [38,39]. Results of the current study suggest that the bioactive compounds from quince and fig would be valuable for their potential use in the prevention and treatment of heart diseases.…”
Section: Discussionmentioning
confidence: 76%
“…likewise, the peel's phenolic acids content (0.77 ± 0.01 mg/g) was significantly higher than the value verified for the pulp (0.542 ± 0.001 mg/g). Dozens of previous studies have evaluated the phenolic constitution of whole figs (fresh and/or dried, from very many varieties), and a great part of these papers comparatively assessed the fruits' peel and pulp fractions, using spectrophotometric and/or chromatographic approaches (Solomon et al, 2006;Del Caro & Piga, 2008;Oliveira et al, 2009;Russo et al, 2014;Kamiloglu & Capanoglu, 2015;Hoxha & Kongoli, 2016;Ajmal et al, 2016;Ammar et al, 2015;Harzallah et al, 2016;Vallejo et al, 2012;Wojdyło et al, 2016;Maghsoudlou et al, 2017;Pereira et al, 2017;Mahmoudi et al, 2018;Meziant et al 2018;Mopuri et al, 2018). In many cases, the TPCs were given in gallic acid equivalents (GAE)/g fw, whereas the TFCs were expressed as mg (+)-catechin equivalent (CE)/g fw.…”
Section: Tablementioning
confidence: 99%
“…In the past years, several groups have investigated the polyphenol constitution of the distinct parts of F. carica fruits (fresh and/or dried) from Israel (Solomon et al, 2006), Italy (Del Caro & Piga, 2008), Portugal (Oliveira et al, 2009), Turkey and Greece (Kamiloglu & Capanoglu, 2015;Russo, Caporaso, Paduano, & Sacchi, 2014), Albania (Hoxha & Kongoli, 2016), Pakistan (Ajmal et al, 2016), Tunisia (Ammar, del Mar Contreras, Belguith-Hadrich, Segura-Carretero, & Bouaziz, 2015;Harzallah, Bhouri, Amri, Soltana, & Hammami, 2016), Iran (Maghsoudlou, Esmaeilzadeh Kenari, & Raftani Amiri, 2017), Spain (Pereira et al, 2017;Vallejo, Marín, & Tomás-Barberán, 2012;Wojdyło, Nowicka, Carbonell-Barrachina, & Hernández, 2016), Algeria (Mahmoudi et al, 2018;Meziant et al 2018), India and South Africa (Mopuri et al, 2018). Some authors have studied the volatile profile of many Portuguese fig cultivars (Oliveira et al, 2010;Rodríguez-Solana et al, 2018), whereas a recent work of our group demonstrated the feasibility of recovering bioactive anthocyanin pigments from the peel of a Portuguese purple fig variety via emerging technologies (Backes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%